Embracing Arms : Cultural Representation of Slavic and Balkan Women in War - Hashamova, Yana; Goscilo, Helena, 1945- (Book collections on Project MUSE., 2012)
Discursive practices during war polarize and politicize gender: they normally require men to fulfill a single, overriding task-destroy the enemy-but impose a series of often contradictory expectations on women. The essays in the book establish links between political ideology, history, psychology, cultural studies, cinema, literature, and gender studies and addresses questions such as- what is the role of women in war or military conflicts beyond the well-studied victimization? Can the often contradictory expectations of women and their traditional roles be (re)thought and (re)constructed? How do cultural representations of women during war times reveal conflicting desires and poke holes in the ideological apparatus of the state and society?